WHEAT research identified factors and business models that positively impacted farmers’ adoption of sustainable intensification and climate smart farming practices in the Indo-Gangetic Plain. - CGIAR Research Program on Wheat (2019)
CGIAR Research Program on Wheat (WHEAT) research identified proven factors and business models that positively impacted farmers’ adoption of sustainable intensification and climate smart farming practices in the Indo-Gangetic Plain. Factors included lower costs, improved access to technologies, social inclusiveness, increased awareness and availability of information, and support to technology providers. These findings helped government agencies prioritize the portfolio of climate smart agricultural practices to maximize crop productivity, profitability and input use efficiency, while improving capacity and reducing environmental footprint.